The relationship between the effective tax rate and the nominal rate - Dias, P. J. V. L.; Reis, P. M. G. (Contaduría y Administración, 2018)
The main goal of this investigation is to understand the relationship between the nominal rate and the effective tax rate and to evaluate if the differences between them depend on the value of the nominal rate. Based on a sample of 1,530 companies from 5 countries members of the European Union (Denmark, Slovenia, Finland, Luxembourg and the United Kingdom) there’s evidence that the effective tax rate is positively related to the nominal rate. The effective tax rate was calculated through the ratio between the value of the tax paid over the result before tax. When the nominal tax rate increases, the effective rate increases equally but with a slower growth. This relationship is softened if we take into account the value of the nominal tax rate, which shows that companies have the ability to manage the results in order to increase savings in tax.